2022
DOI: 10.3389/fimmu.2022.1002163
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin limits age-related expansion of myeloid-derived suppressor cells

Abstract: Aging results in enhanced myelopoiesis, which is associated with an increased prevalence of myeloid leukemias and the production of myeloid-derived suppressor cells (MDSCs). Tristetraprolin (TTP) is an RNA binding protein that regulates immune-related cytokines and chemokines by destabilizing target mRNAs. As TTP expression is known to decrease with age in myeloid cells, we used TTP-deficient (TTPKO) mice to model aged mice to study TTP regulation in age-related myelopoiesis. Both TTPKO and myeloid-specific TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 47 publications
(52 reference statements)
3
12
0
Order By: Relevance
“…27 The present study showed that the expansion of M-MDSCs significantly and adversely affects the skeletal phenotype under conditions of TTP decline, including aging. 26,27 As an RNA-binding protein, TTP functions as a key negative regulator of inflammation by inhibiting the production of multiple pro-inflammatory cytokines. 34 TTP is a key molecular target in the p38 mitogen-activated protein kinase (MAPK)/MAPK-activated protein kinase-2 (MK2) stress signaling pathways with a primary role in binding to adenosine-uridine rich elements (AREs) in the 3′ untranslated regions (3′-UTRs) by virtue of the tandem CCCH zinc finger within target mRNA transcripts, thus destabilizing and promoting mRNA degradation of targets such as TNFα, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…27 The present study showed that the expansion of M-MDSCs significantly and adversely affects the skeletal phenotype under conditions of TTP decline, including aging. 26,27 As an RNA-binding protein, TTP functions as a key negative regulator of inflammation by inhibiting the production of multiple pro-inflammatory cytokines. 34 TTP is a key molecular target in the p38 mitogen-activated protein kinase (MAPK)/MAPK-activated protein kinase-2 (MK2) stress signaling pathways with a primary role in binding to adenosine-uridine rich elements (AREs) in the 3′ untranslated regions (3′-UTRs) by virtue of the tandem CCCH zinc finger within target mRNA transcripts, thus destabilizing and promoting mRNA degradation of targets such as TNFα, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies from our group have shown that altered TTP expression greatly influences bone myeloid stem cell population expansion with concomitant increased M‐MDSCs in peripheral tissues 27 . Because of these observations, we wanted to understand the bone phenotypic changes that may directly or indirectly result from the altered M‐MDSCs expansion and differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations